Hydrothermal synthesis of ternary α-Fe2O3–ZnO–Au nano composites with high gas-sensing performance - Yusuf Valentino Kaneti; Julien Moriceau; Minsu Liu; Yuan Yuan; Quadir, Md Zakaria; Xuchuan Jiang; Aibing Yu (Elsevier, 2014)
This study reports facile hydrothermal strategies for the synthesis of novel ternary α-Fe2O3–ZnO–Au nanocomposites under mild conditions, through further surface coating of ZnO and Au nanoparticles (NPs) on α-Fe2O3 nanorods. The ternary α-Fe2O3–ZnO–Au nanocomposites are found to show (1) higher sensitivity/responses (S) of 113 and 57 toward 100-ppm n-butanol and acetone, respectively compared to single α-Fe2O3 (S = 11.7, 9.1 for n-butanol, acetone) and binary α-Fe2O3-ZnO (S = 54.4, 28 for n-butanol, acetone) sensing materials, and (2) lower optimum operating temperature, i.e., 225 °C. The enhanced sensitivity could be attributed to the chemical sensitization effect induced by the Au NPs, and the existence of conjugated depletion layers in the nanocomposites which promote a greater drop in resistance upon exposure to the gas. These results will be useful for future design of iron oxide-based ternary nanocomposites as gas-sensing materials with high sensitivity, selectivity and stability.